PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KPS SISWA DAN HASIL BELAJAR PADA MATERI ASAM BASA - Rialdi Malau; Anna Juniar (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2020)
This study aims to: (1) To know the student Learning Outcomes that learned by Guided Inquiry were higher than Conventional model, (2) To know the student KPS  improvment that learned by Guided Inquiry were higher than the conventional model, (3) To know the correlation between learning outcomes and KPS of students that learned by Guided Inquiry model . The population of this study is all students of class XI IPA  SMA Budasatria. The sample selection is by total sampling namely XI IPA 1 and XI IPA 2, class XI IPA 1 with the Guided Inquiry learning. The instrument used a learning outcome test in the form of 20 valid multiple choice, the KPS test instrument in the form of an essay test. From t-test with a significance level of 0.05 worth 1.6749 is 9.2 on learning outcomes and 17 on KPS. Then from the Product Moment Correlation test with a significance level of 0.05, the rtable value is 0.37, the rcount is 0.81, so there is correlation between student learning outcomes and KPS. The contribution of learning outcomes to the increase in KPS by 65%.